Pencegahan Bullying Melalui Pendampingan Sosialisasi Anti Bullying Program Rekan School Expedition Yatim Mandiri Mojokerto di SDN Karangkedawang - Zakiyatus Soimah; M. Soleh Mauludin; Syahrur Rizki; Anjas Putra Anjami; Muhammad AzkalAzzkiya'; Hishnun Hashin Al Hidan; Faza Ahmad Bi’auni Rabby (LP3M IAIFA Kediri, 2026)
The Colleague School Expedition Program assistance organized by Yatim Mandiri Mojokerto aims to educate about bullying and violence in the elementary school environment. The method used in this activity is Participatory Action Research (PAR) with stages of planning, implementation, observation and reflection. Socialization is carried out through interactive discussions, fun games, educational videos, and role simulations to increase students' understanding of the types of bullying and how to prevent it. This mentoring was attended by all 185 Karangkedawang Elementary School students. The results of the activity showed an increase in students' understanding of bullying, demonstrated by a positive response to the material presented and instilling a commitment to students to create a school environment that is free from bullying. It is hoped that this assistance will become a model in efforts to prevent bullying in other schools and become a basis for developing school policies that are more concerned with student welfare.